COGNITIVE, CULTURAL, AND TECHNOLOGICAL CONSTRAINTS SHAPING THE TRANSLATION OF CONTEMPORARY MEDIA TEXTS - Erkinjon Kamilovich Satibaldiev (Western European Studies, 2025)
This article examines how translation in contemporary media environments is shaped by the interaction of cognitive, cultural, and technological constraints. As digital ecosystems generate increasingly multimodal and fast-paced communication, translators must navigate complex meaning structures across linguistic, visual, and platform-specific modalities. The study highlights three major domains of influence: cognitive processing limitations imposed by rapid information flow and multimodal density; cultural factors involved in framing, emotional resonance, and audience expectations; and technological constraints produced by algorithmic curation, machine translation integration, and platformdependent textual formats. Drawing on research in media studies, translation technology, and intercultural communication, the article argues that media translation today functions as an adaptive interpretive practice that requires specialized competencies beyond traditional linguistic equivalence. These include multimodal literacy, awareness of platform discourse norms, and the ability to manage accelerated translational cycles. The findings underscore the need for updated methodological models in translation studies that reflect the realities of digital media production
Keywords: multimodality; media translation; digital communication